Comparison of physical fitness levels among practicing and non-jiu-jitsu schoolchildren - Carlos Alberto da Silva; Abraham Lincoln de Paula Rodrigues; Stela Lopes Soares (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2019)
Jiu-Jitsu is a sport that has been growing a lot in recent years. The objective was to compare the levels of physical fitness among practicing and non-practitioners of jiu-jitsu students in a neighborhood in the city of Fortaleza/CE. The following variables were analyzed: BMI, flexibility, abdominal resistance and cardiorespiratory endurance, with 22 children, all males, divided into 2 groups with 11 individuals. It was observed that the Jiu-Jitsu group was better in all tests mainly in the flexibility tests (JJ: 31 (± 2.00), EDF: 28 (± 4,07)) and abdominal resistance (JJ: 30 (± 4,42), EDF: 25 (± 2.99)), where it obtained a significant difference, already in the variables BMI (JJ: 20 (± 2.02) EDF: 22 (± 4,28) and cardiorespiratory Endurance (JJ: 654 (± 127) EDF (583 (± 120)) Although there was no significant difference, the Jiu-jitsu group showed higher values than the EDF group. With the results obtained it can be concluded that the practice of Jiu-jitsu can bring health benefits as good or better than the practice of physical education.